Pathways between socioeconomic status and health: Does health selection or social causation dominate in Europe?. (June 2018) - Hoffmann, Rasmus; Kröger, Hannes; Pakpahan, Eduwin
Abstract: Health differences which correspond to socioeconomic status (SES) can be attributed to three causal mechanisms: SES affects health (social causation), health affects SES (health selection), and common background factors influence both SES and health (indirect selection). Using retrospective survey data from 10 European countries (SHARELIFE, n = 20, 227) and structural equation models in a cross-lagged panel design, we determine the relative importance in terms of explanatory power of social causation and health selection in the life course from childhood to old age. Both SES and health heavily depend on their prior status, albeit more for SES than health. During the transition from childhood to working ages, social causation and health selection are equally weak. Turning to the second phase (transition from working ages to old age) causation increases while selection decreases which makes causation the dominant mechanism in older age. While the contribution of common background factors remains difficult to assess, this study shows that both social causation and health selection are responsible for health inequalities; however, their relative importance changes with age. Life course modelling can complement causal analysis by revealing interactions between the processes of SES and health and their contribution to health inequality.